Variation by ethnic group in premature mortality risk following self-harm: a multicentre cohort study in England - Turnbull, P; Webb, R; Kapur, N; Clements, C; Bergen, H; Hawton, K; Ness, J; Waters, K; Townsend, E; Cooper, J (BioMed Central, 2015)
Background: Incidence and risk factors for self-harm vary according to ethnicity. People who self-harm have been shown to have increased risk of premature death, but little is known about mortality following self-harm in ethnic minority groups. Methods: A prospective cohort study of self-harm presentations to three English cities (Derby, Manchester, Oxford) between 2000 and 2010. We linked to a national mortality dataset to investigate premature death in South Asian and Black people in comparison with White people to the end of 2012. Results: Ethnicity was known for 72 % of the 28,512 study cohort members: 88 % were White, 5 % were South Asian, and 3 % were Black. After adjusting for age, gender and area-level socioeconomic deprivation, the risk of all-cause mortality was lower in South Asian (hazard ratio [HR] 0.51, 95 % confidence interval [CI] 0.42 – 0.62) and Black people (HR 0.46, 95 % CI 0.39 – 0.55) versus White people. Suicide risk was significantly lower in Black people (HR 0.43, 95 % CI 0.19 – 0.97) than in White people. Prevalence of risk factors for premature death, such as previous self-harm, psychiatric treatment or concurrent alcohol misuse, was lower in South Asian and Black people than in White people. Conclusions: The risk of death following self-harm is lower in South Asian and Black people than White people in the UK, and they also have lower prevalence of risk factors for premature death. Awareness of both protective and risk factors might help to inform clinical decisions following assessment.